The interaction of labor market regulation and labor market policies in welfare state reform - Werner Eichhorst; Regina Konle-Seidl (Institute for the Study of Labor (IZA), 2005)
Employment protection legislation, unemployment benefits and active labor market policy are Janus-faced institutions. On the one hand they are devices of insurance against labor market risk that provide income and employment security. On the other hand they influence the capacities of labor markets to adapt to changing economic conditions since institutional features of the welfare state also affect actors' economic adaptation strategies. Insufficient labor market adaptability results in higher and more persistent unemployment. Hence, in order to in-crease the adaptability of European labor markets, reforms had to address these closely inter-acting policy areas. The first aim of the paper is to describe recent reforms of employment protection, unemployment insurance and active labor market policies in different European welfare states (Denmark, Sweden, the United Kingdom, Switzerland, the Netherlands, Spain and Germany). The paper shows whether and to what extent national policy patterns converge in the direction of a new balance of flexibility and security with employment protection being eased and labor market policies being activated through a combination of carrots and sticks. Secondly, in terms of the political economy of welfare state reforms, the paper will answer the question whether consistent reforms of the three institutions are more likely in political systems characterized by relative strong government and/or social partnership since such institutional prerequisites may favor package deals across policy areas.
Keywords: J58; J68; J65; 330; employment protection; labor market policy; unemployment insurance; labor market reform